The Effect of Sustainanbility Report Dislosure Toward Financial Performance (Study on All Companies Except Financial Companies Listed in Indonesian Stock Exchange Period 2014-2016) - Erika Putri Fadilla (Kajian Akuntansi, 2018)
The sustainability report is different from the financial statement. Beside of supporting the sustainable development, this report is expressed as a corporate commitment to the community and the environmental around the company. One of the benefits of disclosure of sustainability report was able to be a media of information for internal and external stakeholders, to assess the social responsibilities that the company performed.The Global Reporting Initiative (GRI) G4 is a guidelines in measuring the sustainability report disclosure, it is consist of 91 item which will be calculated with Sustainability Report Disclosure Index (SRDI). The SRDI calculation is performed by giving a score 1 if an item is disclosed, and 0 if not disclosed. After scoring the entire item,they added to get the total score for each company.Population in this study refers to the all company except non financial companies that listed in Indonesia Stock Exchange Period 2014-2016. The technique used in this study is purposive sampling with 7 samples of the companies were selected which in the period of three years, so there were 21 samples data of companies listed in Indonesia Stock Exchange Period 2014-2016 are used. This study aims to examine the effect partially between Sustainability Report Disclosure to Return On Assets (ROA), Current Ratio (CR), Debt to Equity Ratio (DER) and Inventory Turnover (IT) on companies listed in BEI period 2014-2016. Methods of data analysis in this research is panel data regression analysis using Eviews 10. Based on the result of this research shows that partially Sustainability Report Disclosure have no effect on Return On Asset (ROA), Sustainability Report Disclosure have a positive and significant effect on Current Ratio (CR), Sustainability Report Disclosure have have no effect on Debt to Equity Ratio(DER), Sustainability Report Disclosure have have no effect on Inventory Turnover(IT)